2009
DOI: 10.1002/jsfa.3494
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variation of intestinal skatole production and microbial community in Jinhua and Landrace pigs

Abstract: BACKGROUND: An excessive accumulation of skatole in pigs is a major contributor to boar taint. Intestinal skatole concentrations may vary among different pig segments and breeds. The objective of this study was to evaluate the spatial variation of intestinal skatole production and the microbial community in local Jinhua and exotic Landrace pigs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…(), and Li et al. (), who showed that skatole concentrations increased from the cecum to the rectum in pigs. Similarly, Claus, Weiler, and Herzog () reported the highest skatole levels in the rectum of pigs.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…(), and Li et al. (), who showed that skatole concentrations increased from the cecum to the rectum in pigs. Similarly, Claus, Weiler, and Herzog () reported the highest skatole levels in the rectum of pigs.…”
Section: Discussionmentioning
confidence: 95%
“…Li et al. () previously reported that the total VFA, acetate, and propionate contents significantly vary among the intestinal segments in pigs, generally decreasing from the cecum to the rectum. However, skatole and indole levels gradually increased.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations